Rekrutmen Tenaga Pendidik dalam Peningkatan Mutu Madrasah Aliyah Negeri Insan Cendekia Jambi - K.A. Rahman, Ardiansyah, dan Marwazi (FITK UIN Walisongo, 2015)
The purpose of this research is to know the process of teacher recruitment to improve the quality of Madrasah Aliyah Negeri Insan Cendikia Jambi. The method used descriptively qualitative. Data collection used observation, interview, and document study. The result of the research showed that the process of teacher recruitment whice conducted was good. The recruitment activity was began by planning of teacher need that was by analyzing the present teacher need, the announcement of teacher vacancy, the requirement that should be acquired by teacher candidate, using some test in selection section, and deciding teacheracceptance. Researchers suggested the teacher recruitment activity at MAN Insan Cendikia Jambi should be kept, or improved if possible. Especially in the vacancy announcement extended teacher and files relating to the recruitment of teachers should be archived.AbstrakTujuan penelitian ini adalah untuk mengetahui proses rekrutmen tenaga pendidik dalam peningkatan mutu Madrasah Aliyah Negeri Insan Cendikia Jambi. Metode yang digunakan deskiptif kualitatif. Teknik pengumpulan data menggunakan observasi, wawancara dan studi dokumen. Hasil penelitian menunjukan bahwa proses rekrutmen guru yang dilakukan sudah baik. Kegiatan rekrutmen ini diawalidengan perencanaan kebutuhan guru, pengumuman adanya lowongan guru, persyaratan yang harus dipenuhi calon guru, seleksi dengan berbagai tes, dan penentuan penerimaan guru. Peneliti menyarankan agar kegiatan rekrutmen tenaga pendidik pada MAN Insan Cendekia Jambi di pertahankan, bila perlu ditingkatkan agar lebih baik lagi. Terutama dalam pengumuman lowongan guru diperpanjang dan berkas-berkas yang berkaitan dengan rekrutmen guru sebaiknya diarsipkan.